Impacts of Psychological Distress, Gender Role Attitude, and Housekeeping Sharing on Quality of Life of Gynecologic Cancer Survivors - Gunhee Kim; Moonjeong Kim (Korean Society of Women Health Nursing, 2018)
PURPOSE: To determine impacts of psychological distress, gender role attitude, and housekeeping sharing on quality of life of gynecologic cancer survivors. METHODS: Subjects completed questionnaires consisting of four measurements: FACT-G (ver. 4) for quality of life, anxiety and depression from SCL-90-R for psychological distress, gender role attitude, and housekeeping sharing. A total of 158 completed data sets were analyzed by descriptive statistics, independent t-test, ANOVA, Pearson's correlation coefficient, and multiple regression analysis using SPSS 21.0 program. RESULTS: Quality of life was significantly and negatively correlated with psychological distress (r=−0.64, p < .001), but not with gender role attitude (r=−0.14, p=.820) or housekeeping sharing (r=0.08, p=.350). Psychological distress was significantly and positively correlated with gender role attitude (r=0.25, p < .010). Factors that significantly impacted quality of life were type of cancer (t=2.27, p=.025), number of treatment methods (t=2.58, p=.011), education level (t=3.33, p < .001), and psychological distress (t=−9.96, p < .001). CONCLUSION: Nursing interventions that can relieve psychological distress need to be developed for gynecologic cancer survivors. Nurses need to put priority on ovarian cancer survivors who have low education level with multiple treatment methods when performing nursing interventions to improve the quality of life of gynecologic cancer survivors.